COMPARATIVE ANALYSIS OF TRANSLATION BETWEEN THE SOURCE LANGUAGE (SL) AND THE TARGET LANGUAGE (TL) IN TAGORE’S POETRY: GITANJALI, SONGS OF OFFERINGS - Sumaryana Putra, I Komang; Rahmani Putri, Dian (Lingual Journal of Language and Culture; Vol 4 No 2 (2017)DO - 10.24843/LJLC.2017.v04.i02.p04, 2017)
The long lyrical poem entitled Gitanjali, Songs of Offerings written by Rabindranath Tagore (1861 – 1941) is very interesting and has a deep philosophical thought. In this occasion, Part LVII is selected to be analysed. This poetry was translated into Indonesian by Amal Hamzah in 1952, which is used as the target language (TL). The approach us ed is from literary criticism (intrinsic and extrinsic) and from perspective of translation theories. Based on the analysis, obviously, we can see that a single word may have various senses and those are signalled by the context. Especially in poetry, it is enriched by figurative senses. The process of translating poetry absolutely cannot ignore the message of the source language (SL); however, reminding that there is no 100% synonymy between words in every language, the translating process must notice the intrinsic sight of the poem. We cannot judge whether a translation is bad, better or good, especially translation in poetry, particularly the lyrical poem. In this case, some strategies can be conducted such as: translation shifts, lexical translation, idiomatic translation, borrowing, etc., which can be used to naturalize the poetry translation and to achieve the best readability of the TL text. Keywords: Gitanjali, Lyrical Poem, Source Language, Target Language